A comparative analysis of Bayesian age-at-death estimations using three different priors and Suchey-Brooks standards. (July 2022) - Kim, Jieun; Lee, Sookyoung; Choi, Inseok; Jeong, Yangseung; Woo, Eun Jin
Abstract: This study addresses issues associated with limited access to reference skeletal collections and how it hampers regional methodological development. The study also investigates the effects of three different priors on age-at-death estimations of Koreans and quantifies the accuracy of Bayesian estimation compared to a non-Bayesian approach. CT scan images of pubic symphyses were scored following the Suchey-Brooks standards. We specifically examine Bayesian age-at-death estimations under an optimal scenario where both the likelihood and prior probability are derived from a target population of Korean origin. Three different priors (population, forensic, and uniform priors) are evaluated for their age estimation accuracy levels. The results showed that Korean males and females had discrepancies in skeletal aging rates only in certain phases. A similar trend was observed in the comparison of the original Suchey-Brooks and Korean sample aging rates. However, when final age estimates were computed based on an inadequate choice of a prior, the between-group differences may be minimized or even obscured. The uniform and forensic priors produced the most reasonable and unbiased estimates, while the uniform prior consistently provided open-ended estimates for the last phase. The population prior produced consistently higher estimates due to the high survivorship of Koreans. In addition, the original Suchey-Brooks standards persistently under-estimated ages for Korean males and females. Overall, when Bayesian age estimation is based on an informed prior that best matches the context of the case (forensic deaths in this study), there was increased accuracy of final age estimates compared to age estimates of other priors and the original Suchey-Brooks method. Highlights: MDCT scans can be utilized for age estimation using the pubic symphysis morphology. Suchey-Brooks' age estimation method consistently underestimates age for Koreans. Bayesian methods with proper priors outperform frequentist approaches in Koreans.